Pengembangan Media Pembelajaran Fisika Berbasis Kecerdasan Buatan (AI) Terintegrasi Bakpia: Uji Kelayakan Ahli - Bayu Setiaji; Ela Nur Fatmah; Pujianto Pujianto; Riki Perdana; Nia Fitrotul Mas'ulah; Hanifah Nauli; Anindita Putri Canina Pitono; Febrina Siska Widyaningtyas; Yusman Wiyatmo (Postgraduate, University of Mataram, 2025)
This research aims to develop AI-based learning media integrated with the concept of bakpia in learning Physics on the topic of Temperature and Heat for students in senior high school. The research method used is the research and development (R & D) method with the 4D model modified into 3D, namely define, design, and develop because the main focus is the feasibility test. The integration of the bakpia concept with AI, Perplexity and ChatGPT, is in one phase of the syntax of the learning model that exists in each learning media. The resulting product has been tested and assessed through a feasibility test by 2 validators, namely lecturers who are material experts and media experts. The feasibility test results of learning media on the topic of Temperature and Heat in the form of E-Worksheet was 1.97, E-Module 1.84, and E-Book 2.01, all of which are in the feasible category. Based on this, it can be concluded that the AI-based learning media integrated with the bakpia concept on the topic of Temperature and Heat developed can improve the physics identity and 21st century skills of students in Senior High School as measured by questionnaires, observations, and written tests when this product is developed more widely